Post-traumatic stress disorder: update on diagnosis and treatment. (May 2021) - Morganstein, Joshua C.; Wynn, Gary H.; West, James C.
SUMMARY: Post-traumatic stress disorder (PTSD) is a common trauma and stressor-related disorder. Trauma-focused psychotherapies and selective serotonin reuptake inhibitors represent current state of the art treatment for PTSD, with current evidence favouring psychotherapy as first-line treatment. Much room remains for development of more effective therapeutics. This article give a brief update on diagnosis and treatment of PTSD.